Origin of Non-axisymmetric Features of Virgo Cluster Early-type Dwarf Galaxies. I. Bar Formation and Recurrent Buckling - Kwak, SungWon; Kim, Woong-Tae; Rey, Soo-Chang; Kim, Suk (The Astrophysical journal, 2017)
A fraction of early-type dwarf galaxies in the Virgo cluster have a disk component and even possess disk features such as bar, lens, and spiral arms. In this study, we construct 15 galaxy models that resemble VCC856, which is considered to be an infalling progenitor of disk dwarf galaxies, within observational error ranges, and use N-body simulations to study their long-term dynamical evolution in isolation as well as the formation of bar in them. We find that dwarf disk galaxies readily form bars unless they have an excessively concentrated halo or a hot disk. This suggests that infalling dwarf disk galaxies are intrinsically unstable to bar formation, even without any external perturbation, accounting for a population of barred dwarf galaxies in the outskirts of the Virgo cluster. The bars form earlier and stronger in galaxies with a lower fraction of counter-streaming motions, lower halo concentration, lower velocity anisotropy, and thinner disk. Similarly to normal disk galaxies, dwarf disk galaxies also undergo recurrent buckling instabilities. The first buckling instability tends to shorten the bar and to thicken the disk, and drives a dynamical transition in the bar pattern speed as well as mass inflow rate. In nine models, the bars regrow after the mild first buckling instability due to the efficient transfer of disk angular momentum to the halo, and are subject to recurrent buckling instabilities to turn into X-shaped bulges.